Analyzing the most prominent issues during rehabilitation process of abandoned housing project - Siti Farhana, Shammudi (2019)
The issue of abandoned building happens across the globe, and it brings nothing positive to the stakeholders as well as to the country economy. In Malaysia, this issue has grown to an unbearable state, and this study aims to study the abandoned building in Malaysia. Abandoned was the project including the building, civil engineering and heavy engineering development project for example houses, schools, bridges, roads, high rise building and others that been abandoned. The issue of abandoned projects is still an unsettled issue in Malaysia. Although there are abandoned projects that has been revived successfully, but there are projects that are still being revived or being considered to be revived. At the same time there are number of abandoned projects which has not yet come close to the consideration stage, due to some reasons such as the possibility of project revival is slim as there are no companies that are interested in investing on the revival of abandoned projects. Even though there are numerous policies and laws have been promulgated by the Malaysian government, yet the problem of abandoned housing projects is still occurring and has not yet been fully addressed. In this study, questionnaires and literature studies were conducted to assess the issues that arise in the rehabilitation of abandoned housing projects. The expected outcomes of this study are to provide preventive measures for reviving issues and solutions to abandoned buildings in Malaysia. The expected outcomes of this study are to provide methods of prevention for the issue and reviving solutions to the abandoned building in Malaysia. Minimum 50 questionnaires surveys were distributed randomly to contractor, consultant, developer, government, and others. The questionnaires forms were distributed through the social network, e-mail and also by hand using questionnaire form. The 34 sets of questionnaire were used and as the analyzed in this research. Relative Index Inequality (RII) is adopted to evaluate the ranking of different factors by the respondents. From the findings of the study, management, financial and legal issues are the major issues that cause the abandonment of the abandoned project cannot be carried out quickly and perfectly so the number of abandoned projects cannot be reduced. The precautionary steps should take before start the project to avoid the abandoned housing project happen, where the legality of the developer should be tracked.